Performance of Insurance Agent Perspective of Work-Life Balance (WLB) - Ali Jufri; Pebi Kurniawan; Imam Hadiwibowo; Sari Laelatul Qodriah; Ronald Swarea Rae (Universitas Medan Area, 2023)
This study explicates the aspects of work-life balance that occurred in the work environment during the Covid 19 pandemic. Covid-19 has changed the work patterns mostly carried out from home utilizing virtual media which in turn exert influence on the performances of the agent PT. BRI Cirebon Life Insurance. The quantitative method with descriptive and verification research types was applied in this study using the saturated sampling technique by employing all of the population. A total of 63 respondents of working agents at PT. BRI Cirebon Life Insurance were involved. The data analysis technique was focused on analyzing the multiple linear regression, the coefficient of determination, the simultaneous, and the partial aspects. The calculation method is supported by the use of the SPSS 25 program. The results obtained from this study pinpoint that job performances were significantly affected by each dimension of Work-Life Balance (WLB) such as the Time Balance, the Involvement Balance, and the Satisfaction Balance. In addition, those three aspects simultaneously and significantly influence the employees’ performances. At last, the findings signify that delays in awarding and the time flexibility impeded the performance of the agents. Some proposed actions are recommended to help the employees work optimally.